A new year, a new challenge, a new COVID-19 variant - Eka Sakti Wahyuningtyas; Djeneba Traore (Journal of Holistic Nursing Science, 2022)
It has been one year since the Coronavirus become a pandemic worldwide. Studies highlighted that various measures have been well conducted to reduce the transmission of COVID-19. Recently, World Health Organization (WHO) announced a new COVID variant named Omicron which is initially reported in South Africa. As a result, the challenge is getting more difficult as viruses continuously mutate. The pandemic situation demand nurses to gain competencies in delivering innovative care for patients with COVID-19 infection. Keywords: COVID-19; Omicron; nursing services; health promotion; prevention; virus mutation